Sentimental value [videorecording (Blu-Ray)] - Trier, Joachim; Vogt, Eskil; Reinsve, Renate; Skarsgård, Stellan; Fanning, Elle, 1998-; Lilleaas, Inga Ibsdotter, 1989- (Criterion collection., 2026)
Joachim Trier, one of contemporary cinema's great humanists, excavates layers of history and memory both national and personal for this rich, ineffably moving story of one family's attempts to come to terms with generations of trauma and healing. After the death of their mother, two sisters must contend with the return home to Norway of their estranged father, celebrated filmmaker Gustav Borg. In the case of Nora, an actor, he hopes to reconnect by casting her in his new film a project that both inflicts fresh wounds and reopens old ones.